STRATEGI GURU DALAM MENINGKATKAN PEMBELAJARAN KEMAMPUAN MEMBACA PESERTA DIDIK KELAS II SEKOLAH DASAR NEGERI 238/VI TANJUNG PUTUS II - Riyadi Saputra; Dwi Novri Asmara; Rahmania (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to improve students' reading skills because there are obstacles in reading at the beginning of grade 2 students. Therefore the teacher applies strategies that can make students more easily and actively participate in learning to read so that students can learn easily and have fun. This study uses a qualitative descriptive research approach with a phenomenological research type. This research was conducted at SDN 238/VI Tanjung Putus II, Tanjung Putus Village, West Tabir District, Merangin Regency, Jambi Province. The data in this study uses primary and secondary data. Data collection techniques used in the form of observation techniques Interview Methods (interviews) and documentation. The data validation technique in this study went through three stages, including the preliminary stage, the filtering stage and the incomplete data completion stage. The data analysis technique used was analysis during data collection and analysis after the data was collected. The results of this study showed that the beginning reading ability of grade 2 students at SD Negeri 238/VI Tanjung Putus II was still low and there were several students who needed guidance and assistance from the teacher in reading. . 2) The strategy used in the process of implementing improving students' reading skills is the bottom-up strategy. Implementation of the strategy using the basal readers method is a series of reading activities carried out after students know and understand various forms of letters and various series of variations of combining letters into various words. Then proceed with using the distar method, the teacher also applies a peer tutor approach by asking students who are already fluent in reading to help their friends who can't yet. 3) The impact of using the early reading learning strategy in grade 2 is an increase in reading ability which is marked by students being able to read and write independently, only constrained in reading consonants. After the process of reading activities, students also dare to retell what they have read.